Mitigating the Impact of the Global Economic Crisis on Household Health Spending - Docteur, Elizabeth (World Bank, Washington, DC, 2012)
The ongoing financial and economic crisis has hit hard the lives of citizens in Eastern Europe and Central Asian (ECA) countries. Economic growth has started to dip, unemployment is rising and government revenues are expected to fall. The crisis is having a direct impact on the ability of households to pay for health care, a situation that will likely be exacerbated as real government spending on health care declines in many countries due to reduced revenues from the general government budget and payroll-funded health insurance. Patients may have to pay higher prices for health care, make do with reduced access to necessary health services and medicines, and face other health-related financial hardships as well. This brief draws on the experience of countries (outside ECA) in coping with public financing shortfalls, to provide suggestions for mitigating the impact on ECA households of reduced public health spending. First, however, it is important to examine private health spending patterns in the ECA region.